Human immunodeficiency virus-1 core: The Trojan horse in virus–host interaction - Wang, Wei; Li, Yan; Zhang, Zhe; Wei, Wei (Frontiers in Microbiology, 2022)
Human immunodeficiency virus-1 (HIV-1) is the major cause of acquired immunodeficiency syndrome (AIDs) worldwide. In HIV-1 infection, innate immunity is the first defensive line for immune recognition and viral clearance to ensure the normal biological function of the host cell and body health. Under the strong selected pressure generated by the human body over thousands of years, HIV has evolved strategies to counteract and deceive the innate immune system into completing its lifecycle. Recently, several studies have demonstrated that HIV capsid core which is thought to be a protector of the cone structure of genomic RNA, also plays an essential role in escaping innate immunity surveillance. This mini-review summarizes the function of capsid in viral immune evasion, and the comprehensive elucidation of capsid-host cell innate immunity interaction could promote our understanding of HIV-1’s pathogenic mechanism and provide insights for HIV-1 treatment in clinical therapy.